2019
DOI: 10.1002/clc.23257
|View full text |Cite
|
Sign up to set email alerts
|

Risk of ischemic stroke and utility of CHA2DS2‐VASc score in women and men with atrial fibrillation

Abstract: Background The magnitude of increased risk of stroke in women with atrial fibrillation (AF) remains uncertain. Hypothesis We investigated the risk of ischemic stroke and death in women and men with AF, and the risk associated with individual non‐sex CHA2DS2‐VASc risk factors. Methods Retrospective cohort study of 231 077 (48.1% women) nonselected patients with AF not receiving oral anticoagulation from 2006 to 2014. Data from cross‐linked national Swedish registers. The outcome was the first occurrence of isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
0
17
2
2
Order By: Relevance
“…Female sex was neither associated with clinically overt nor with silent ischemic brain lesions in our cohort, which is in contrast to other reports suggesting that women have a higher risk of (overt) stroke than men ( 15 , 22 ). Regarding silent ischemic brain lesions, analyses from the Atherosclerosis Risk in Communities Study showed that female sex was not related to an increased risk of silent brain infarcts ( 23 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Female sex was neither associated with clinically overt nor with silent ischemic brain lesions in our cohort, which is in contrast to other reports suggesting that women have a higher risk of (overt) stroke than men ( 15 , 22 ). Regarding silent ischemic brain lesions, analyses from the Atherosclerosis Risk in Communities Study showed that female sex was not related to an increased risk of silent brain infarcts ( 23 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, in our cohort, although associated with clinically overt ischemic brain lesions, hypertension was not associated with silent brain lesions. This finding may be explained by the fact that measured systolic blood pressure in our cohort was nearly 20 mmHg lower compared to other study populations (20,21) Female sex was neither associated with clinically overt nor with silent ischemic brain lesions in our cohort, which is in contrast to other reports suggesting that women have a higher risk of (overt) stroke than men (15,22). Regarding silent ischemic brain lesions, analyses from the Atherosclerosis Risk in Communities Study showed that female sex was not related to an increased risk of silent brain infarcts (23).…”
Section: Discussioncontrasting
confidence: 98%
“…In a large Swedish cohort of unselected AF patients, Tomasdottir et al showed that associated stroke rates were different when using a point-based approach than when using a disease-specific risk factors approach stratified according to sex. 28 They argued that the excess stroke risk observed among females was score level dependent, but this itself does not allow inference on the magnitude of excess risk that female sex contributes within each level of the score.…”
Section: Stroke Rate Contribution From the "Sex Category" Criterionmentioning
confidence: 99%
“…Some studies support the existence of a sex-specific stroke risk variation according to CHA 2 DS 2 -VASc score levels. 28,30 These observations have led to the implementation of the CHA 2 DS 2 -VA score as the preferred stroke risk score for guiding anticoagulation decisions in patients with AF in the recent guidelines from Australia and New Zealand, 31 despite the lack of any comparative formal risk score validation. Although tempting, the maneuvre of completely ignoring the well-established sexdifferences in stroke risk may have deleterious consequences.…”
Section: Potential Clinical Consequences Of Changing the Risk Scorementioning
confidence: 99%
“…Men and women differ in their clinical risk factors with respect to various predictors of severity among AIS patients. [ 6 ] While the exact reason for this phenomenon is not clear, some studies have reported a correlation between stroke and changes in arterial structure and that biochemical variables including triglyceride level and total cholesterol levels may contribute to stroke severity. [ 7 ] While the role of triglycerides in the risk of ischemic stroke remains controversial, [ 8 , 9 ] a strong association between elevated levels of triglycerides and increased risk of ischemic stroke in men and women in the general population has been reported.…”
Section: Introductionmentioning
confidence: 99%